The Interpretation of Song Lyrics by Fortwnty in the Album Nalar: A Study of Riffaterre's Semiotics - Survey Sijabat; Evelin Giovani; Ekfindar Diliana (Musamus Journal of Language and Literature, 2023)
The purpose of this research is to know the interpretation meaning behind “Kursi Goyang”, "Larasuka", and "Mangu" lyrics by Fortwnty in the Nalar album. This research used a semiotic analysis approach developed by Michael Riffaterre. This semiotics helps researcher to investigate the interpretive meanings of the lyrics of "Kursi Goyang", "Larasuka", and "Mangu". The research process involves four stages, (1) Heuristic and Hermeneutic Readings, (2) Matrices, Variants, and Models, (3) Hypograms, and (4) Indirect Expressions. This research used a qualitative interpretive. The research data were obtained from the lyrics. The data were collected using listening and note-taking technique. The results of the research are from hermeneutic reading in the lyrics “Kursi Goyang” is interpreted when someone is so focused on making money and thinks that happiness comes from having a lot of money and a high position that they forget to take a break. The results of the research are from hermeneutic reading in the lyrics “Larasuka” interpreted as how lonely someone feels, and from hermeneutic reading in the lyrics “Mangu” interpreted as a romantic relationship between individuals who have different religious beliefs. The finding revealed there are three factors that cause indirect expressions named displacing of meaning, distorting of meaning, and creating of meaning.